Political economy and international economics - Bhagwati, Jagdish N.; Irwin, Douglas A. (Cambridge, Mass. : MIT Press, 1991)
This collection of essays is somewhat more diverse than previous ones. New essays on theoretical topics featured in prior volumes appear in this one as well. Bhagwati's more recent interests, however, have been in the theory and political economy of economics and policy.
Includes bibliographical references and indexes.
rpm 23/08/16
Loans
Keywords: Protectionism; Free trade; International trade; Developing countries